The research aims DIVERSIFICATION STRATEGY, INTELLECTUAL CAPITAL, CSR TO FIRM VALUES - Mary, Hilda; Indriyenni (Universitas Sarjanawiyata Tamansiswa, 2024)
The research aims to determine how much influence diversification strategy, intellectual capital, corporate social responsibility have on firm value, with CGC as the moderating variable. The research sample was 70 manufacturing companies listed on the IDX from 2015 to 2019, using a random sampling technique. Tthe results of research, it shows that the diversification strategy has no significant effect on firm value, intellectual capital has no significant effect on firm value, corporate social responsibility has a significant negative effect on firm value, corporate governance as a moderating variable strengthens the relationship of diversification strategy on firm value, corporate governance as a variable moderation weakens the relationship between intellectual capital and company value, corporate governance as a moderating variable weakens the relationship between corporate social responsibility and firm value.